Occupational Stress and Coping Strategies among Self Financing Arts and Science College Faculties in Erode (International Journal of Scientific Research and Management (IJSRM), 2023)
The aim of the study is to find out the stress management level of arts and science college teachers in Erode City. The teachers are the assets of any country. They are burdened with the greatest responsibility of ‘Nation Building’. The teaching profession has an esteemed place among all professions. However, teaching as a profession at any level is becoming more demanding day by day. Teaching has also become more like a managerial job and is having multi-dimensional job responsibilities. Stress can’t be avoided, but one can learn how to manage it. Policy makers are advised to analyze the college teacher training and assessment system with the assumption that personal and social characteristics and working conditions may have an effect on college teacher stress. The present paper discusses the various emerging issues of occupational stress among faculties of higher education in India and required management strategies to handle them. Sample teachers were selected for simple random sampling by using lottery method because of easy accessibility and affordability analyzed by using statistical package of simple percentage and chi square analysis.